THE EFFECT OF STORYTELLING METHOD ON STUDENTS’ LEARNING OUTCOMES OF SDN 2 BANGUN JAYA - Sevtiana, Maya; Hatim, Magdad; BZ. Septeiyawan Abdullah (Universitas PGRI Palembang, 2024)
This research aims to determine the effect of the storytelling method on the learning outcomes of second grade elementary school students. The data collection technique used in this research was an essay test. This research uses a type of experimental research with a pre-experimental design. Data analysis used the SPSS program with Cronbach's alpha test. The results of this research show that there is a significant influence on students' listening learning outcomes. By using the t-test formula, it can be seen that the calculated t value is 7.437 at a significance level of 0.05, resulting in a t table of 2.051. Therefore, t count > t table at a significance level of 0.05, then Ho is rejected and Ha is accepted, which means that there is an influence of the application of the storytelling method on the listening learning of class II students at SDN 2 Bangun Jaya.